1996
DOI: 10.1111/j.1439-0450.1996.tb00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Stages of Rabbit Haemorrhagic Disease Virus Infection Monitored by Polymerase Chain Reaction

Abstract: Summary In order to define more accurately the initial events that take place during rabbit haemorrhagic disease virus (RHDV) infection, different organs of experimentally infected rabbits were analysed for the presence of the virus and correlated with histopathological observations. A total of 24 rabbits were intranasally inoculated with a viral suspension, and tissue samples were taken from the liver, spleen, kidney, lung, thymus, lymph node and tonsil at different intervals post‐inoculation (2, 4, 6, 12, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
17
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
4
17
1
Order By: Relevance
“…These cells could be a primary site of viral replication. This is in agreement with the fact that tracheitis is a frequent early sign of the disease (6,24,27). We were able to observe that both native and recombinant virus particles can attach to them through recognition of A or H type 2 antigens.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…These cells could be a primary site of viral replication. This is in agreement with the fact that tracheitis is a frequent early sign of the disease (6,24,27). We were able to observe that both native and recombinant virus particles can attach to them through recognition of A or H type 2 antigens.…”
supporting
confidence: 75%
“…Death is the result of a widespread circulation dysfunction associated with disseminated intravascular coagulation and necrotizing hepatitis lesions (14,24). Large quantities of virus particles are found in several organs, especially the liver, which is considered the major site of virus replication (6,14,19,27). The viral genome consists of a single-stranded RNA of nearly 7.5 kb, packaged in a small icosahedral capsid (3,15).…”
mentioning
confidence: 99%
“…Specific primers ( Table 1) enabling amplification of the 3' end of the RHDV polymerase gene (POL) and the full capsid protein (VP60) gene were synthesised according to the primer sequences (4,5,15,21,22,25). The following thermal profiles were applied: 94°C for 3 min, 35 cycles of 94°C for 1 min, 55°C for 1 min, 72°C for 1 min, and a final extension at 72°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…This single-stranded nonenvelope RNA virus has a 7.5-kb genome and a 2.2 kb subgenome well packaged in a 27 to 35 nm (in diameter) icosahedral capsid with a major structural protein of about 60 kDa (VP60), and 10 peripheral cup-shaped depressions [12,20]. The ability to agglutinate human erythrocytes of group O, A, B and AB were reported [12,15,20].Detection by reverse transcriptase-polymerase chain reaction (RT-PCR) in a rabbit inoculation model showed that the RHDV RNA was present as early as 18 hr post inoculation (HPI) in the liver and spleen, whereas thymus, kidney, tonsil and lymph node were found to be positive after more than 26 HPI [21] or 36 HPI [9]. Liver was considered to be the major organ for RHDV replication [8,10].…”
mentioning
confidence: 99%
“…Detection by reverse transcriptase-polymerase chain reaction (RT-PCR) in a rabbit inoculation model showed that the RHDV RNA was present as early as 18 hr post inoculation (HPI) in the liver and spleen, whereas thymus, kidney, tonsil and lymph node were found to be positive after more than 26 HPI [21] or 36 HPI [9]. Liver was considered to be the major organ for RHDV replication [8,10].…”
mentioning
confidence: 99%